Aerosol effect on the mobility of cloud droplets. (14th October 2015) - Koren, Ilan; Altaratz, Orit; Dagan, Guy
Abstract: Cloud droplet mobility is referred to here as a measure of the droplets' ability to move with ambient air. We claim that an important part of the aerosol effect on convective clouds is driven by changes in droplet mobility. We show that the mass-weighted average droplet terminal velocity, defined here as the 'effective terminal velocity' ( η ) and its spread ( serve as direct measures of this effect. Moreover, we develop analytical estimations for η and to show that changes in the relative dispersion of η ( can serve as a sensitive predictor of the onset of droplet-collection processes.